Nonlinearity of mechanical behavior of 3D-reinforced composites under compression (Fracture and Structural Integrity, 2023)
Modern technological capabilities make it possible to produce 3D spatially-reinforced for polymer composite materials. The tasks of experimental research and analysis of the deformation process of new composite materials for aviation purposes taking into account the nonlinearity of mechanical behavior become actual.The paper presents an experimental study of the mechanical compression behavior of composite material specimens made of 3D woven carbon fiber preforms using the pressure impregnation technology (Resin Transfer Molding method with a pairwise interlayer reinforcement and a longitudinal layer). Compression mechanical tests were carried out on specimens using a universal system of electromechanical testing Instron 5882 and a system of 3D analysis of displacement and strain fields on the surface. Tests were conducted in accordance with ASTM D 3410 recommendations and using specialized tooling. Consideration of nonlinearity parameter during experimental data processing is proposed. The importance of determining the values of critical deformation in compression as a parameter characterizing the moment of the beginning of fracture is noted. Comparison of carbon fiber composite materials made by the same technology from fibers and binders of different manufacturers has been carried out. The experimental diagrams "stress-strain" and their approximating dependences taking into account the nonlinearity function w are obtained. The type of functions w of the studied materials is defined, the linear approximation of dependence of functions w on deformation is substantiated. Values of strength limits, elastic modulus, nonlinearity coefficient and critical damage were obtained, statistical processing of the obtained results and their analysis were carried out.
Keywords: Carbon-fiber composite; Polymer binder; Spatially reinforced composite; Nonlinearity; Mechanical behavior; Compression; Strength; Digital image correlation